Catch, release and second chances: exploring the impact of angling on two coastal fish species - Andrea Petetta; Daniel Li Veli; Mario La Mesa; Fabio Grati; Luca Bolognini (Frontiers in Marine Science)
We addressed the impact of angling in two Mediterranean inshore sites by conducting a tag-recapture study on caught-and-released black scorpionfish (Scorpaena porcus) and giant goby (Gobius cobitis). We assessed the relationship between the fish vitality at release and the main factors affecting it, i.e. air exposure time, water temperature, fish length and handling. Then, we used conventional fish tags to study fish survivability to catch and release, growth rates, behaviour and site fidelity. Overall, 17 species (mainly gobids and sparids) were caught, with differences in species composition and abundance between the two sites, probably related to their different depth range. A total of 136 individuals of S. porcus and 38 of G. cobitis were caught, tagged and released. S. porcus had a better vitality than G. cobitis once released, which was negatively associated with an increase in air exposure time, although not significant. We recorded 34 recapture events, with a resulting recapture rate of 19.9% for S. porcus (without considering multiple recaptures) and 5.3% for G. cobitis. The length-weight relationship revealed an isometric growth in both species. The von Bertalanffy growth parameters (± standard error) estimated for S. porcus were L∞ = 26 cm ± 5.25 and k = 0.21 ± 0.09, with no significant differences detected in growth rate between immature and mature individuals. The species’ high site fidelity and resilience to catch-and-release indicate its potential susceptibility to repeated angling in confined coastal habitats. These results highlight the need to account for the cumulative ecological impacts of recreational fisheries in the management of coastal fish populations.